Inpatient dialectical behavior therapy combined with trauma-focused therapy for PTSD and borderline personality disorder symptoms: study design of the naturalistic trauma therapy study - Annemieke C. Kamstra; Annemieke C. Kamstra; Sybolt O. de Vries; Maarten F. Brilman; Petty Vasilev; Manna A. Alma; Antoinette D. I. van Asselt; Antoinette D. I. van Asselt; Mia De Wolf; Robert A. Schoevers; Frederike Jörg (Frontiers in Psychiatry)
IntroductionChildhood traumatization can result in physical and mental health problems in adulthood, such as post-traumatic stress disorder (PTSD), which negatively influences quality of life and social functioning. Although evidence based trauma treatments benefit clients with PTSD after childhood abuse and comorbid personality disorders, they are less effective than in clients who were traumatized in adulthood, and drop-out is substantial. The current study aims to assess the effects of inpatient dialectical behavior therapy combined with prolonged exposure (DBT-PTSD) on severity of PTSD, dissociation, parasuicidal behavior and borderline personality disorder (BPD) in clients with severe PTSD and comorbid psychiatric disorders. Secondary outcomes are social functioning, quality of life, borderline and cluster C personality disorder symptoms as treatment predictors, treatment trajectories, clients’ experiences and health economic consequences.MethodsThe naturalistic, longitudinal Trauma Therapy Study is conducted from January 2019 until May 2025 in a mental healthcare center in the Netherlands. Clients with severe PTSD and comorbid conditions who are referred to inpatient DBT-PTSD are included into the study. Based on power analyses a total sample size of N=56 is needed. Measurements take place before the waiting list period, at pre- and posttreatment and at six- and twelve-months follow-up. Clients fill in a daily DBT-PTSD diary, which gives insight into individual symptom trajectories.ResultsStatistical analyses include two-sided paired samples t-tests, linear mixed model analyses and cost-effectiveness analyses. Qualitative interviews are conducted within two years posttreatment and analyzed using a phenomenological approach. We correct for chance capitalization by using a conservative α-level of.01. Multiple imputation is used to handle missing data.DiscussionResearch on the effects of integrated treatment programs for clients with severe PTSD and co-morbid conditions is scarce. This study extends current knowledge on the effects of inpatient DBT-PTSD on PTSD and BPD symptoms, clients’ social functioning and quality of life. In addition, it provides insight into individual symptom trajectories and experiences, inspiring future treatment improvements for clients with severe psychopathology.Trial registrationMedical Ethical Committee approval (NL669060018, RTPO1044/01.10.2018). Preregistration: Dutch registration database Centrale Commissie Mensgebonden Onderzoek and International Clinical Trials Registry Platform (NL-OMON46167/01.10.2018/https://trialsearch.who.int/Trial2.aspx?TrialID=NL-OMON46167).